La tecnología de la información y comunicación en la educación, en el proceso de enseñanza aprendizaje en los estudiantes de básica de la Escuela Alfredo Noboa Montenegro de Caluma Provincia Bolívar - Baños Reyes, Irma Alexandra (2019)
The purpose of this research project refers to information technology and communication in education, the teaching process, learning in the students of the basic school Alfredo Novoa Montenegro of Caluma province Bolívar. In this project, information and communication technology is proposed as one of the most important aspects in the educational field that allows the teaching-learning process to be carried out. The success of teaching in education is not simply the domain of knowledge now is the domain of learning. At present, the importance of incorporating information and communication technologies (ICT) into education has been debated, since through them learning is promoted, because the active and participative construction of students' knowledge; They have a function of being a means of communication and exchange of knowledge and experiences, as well as being an instrument for information, a source of resources, educational spaces and cognitive development. The ideas in the teaching-learning process, technology has become an indispensable tool in educational institutions, allows to obtain new opportunities for teachers, interact ideas, methods to favor decision making in the face of educational needs, allows training focused mainly on the student who interacts acquiring new knowledge. This technology allows that the important thing is the application of the methods, the way of teaching and of learning to use the didactic resources, which provides a quality education, and the learning process.